Tradução, adaptação transcultural e validação do pain attitudes questionnaire para o português brasileiro em pacientes com dor oncológica - GUEDES, César Leonardo Ribeiro (2024)
Objective: To carry out the translation, cross-cultural adaptation and validation into Brazilian Portuguese of the Pain Attitudes Questionnaire – Revised (PAQ-R) in cancer pain patients. Methods: The research was carried out at the Cancer Hospital of Maranhão and Aldenora Bello Hospital (São Luís, MA, Brazil), after approval by the institution’s research ethics committee. In addition to the PAQ-R, the following instruments were applied: Barthel Index, Hospital Anxiety and Depression Scale (HADS), Edmonton Symptom Assessment System (ESAS) and Pain Catastrophizing Scale (PCS). The measurement properties evaluated in the present study were: crosscultural validity, structural validity, construct validity, reliability and internal consistency. Results: The research consisted of 165 cancer patients. The average age of the individuals in the research was 49 years old, with a predominance of women (63%), married (59.9%) and with basic education (53.3%). 33 different types of cancer were identified, the most prevalent being cervical cancer (23%) and breast cancer (9.1%). The internal structure of the PAQ-R with 5 domains and 23 items proved to be adequate. Adequate test-retest reliability and internal consistency were observed. In construct validity, we observed the expected magnitude of the correlation between all domains of the PAQ-R and functional independence, between the stoic strength domain of the PAQ-R and depression, and between catastrophizing and the domains of stoic strength, stoic superiority and cautious doubt of the PAQ-R. No floor and ceiling effects were observed in the studied sample. Conclusion: The Brazilian version of the PAQ-R with 5 domains and 23 items presented adequate construct validity, reliability and internal consistency for patients with cancer pain.